La tutela dei minori nell’ordinamento vaticano (Stato, Chiese e pluralismo confessionale, 2020)
Sommario: 1. Introduzione - 2. La normativa precedente alla Legge n. VIII - 3. Il Titolo II della Legge n. VIII del 2013 - 4. I provvedimenti del 26 marzo 2019 - 5. Conclusioni.The protection of minors in the Vatican legal systemABSTRACT: In recent decades, the sensitivity of public opinion and governments on the subject has increased considerably, new and more restrictive rules have been issued all over the world regarding the protection of minors and the most vulnerable people. Even the Vatican City State has proceeded to integrate its own legal system integrating it with specific new crimes that now allow to offer complete protection of the victims. The contribution analyzes the rules in the penal code and those recently introduced in 2013 and 2019, trying to give an overview of the various measures taken.